New species and taxonomic notes of scaly crickets (Orthoptera: Mogoplistidae: Mogoplistinae) from Borneo - Tan, Ming Kai; Japir, Razy; Chung, Arthur Y. C.; Wahab, Rodzay Bin Haji Abdul (Zootaxa, 2021)
Recent orthopteran surveys in the hyper-diverse Borneo, i.e., Brunei Darussalam and Sandakan in Sabah, allow us to review the scaly crickets from the subfamily Mogoplistinae there. We discover and describe the male, as well as formally naming Cycloptiloides bimaculata Tan, Japir & Chung, sp. nov. from Sandakan. This species was previously described as sp. 1 in a comprehensive revision by Ingrisch (2006) but only the females were known. We also describe Ectatoderus nigrofasciatus Tan & Wahab, sp. nov. from Brunei Darussalam. New locality records are reported for Apterornebius kinabalu Ingrisch, 2006 in Sandakan (Sabah) and Ornebius pullus Ingrisch, 2006 in Belait District (Brunei).